Rethinking Specialisation and the Sexual Division of Labour in the 21st Century - Peter Siminski; Rhiannon Yetsenga (Institute of Labor Economics (IZA), 2020)
This paper aims to shed new light on explanations for the sexual division of labour, within a broader examination of within-household specialisation. We propose a set of indices which we believe are the first direct within-couple measures of specialisation. We use these to present a rich descriptive profile of specialisation. Absolute advantage in market work has only a small role in behaviour for heterosexual couples, and no role at all for same-sex couples. In contrast, sex-based specialisation is much greater. We consider whether the patterns in the data are consistent with a formal Beckerian model of comparative advantage. A woman would need to be 109 times more productive in market work than her male partner before reaching expected parity in domestic work, and this is likely biased downwards due to endogeneity of relative wages related to earlier time use decisions.
Keywords: D13; J16; 330; sexual division of labour; family economics; specialisation; gender; time use